Variations in opening and closing forms in email correspondence in Danish and Swedish - Thode Hougaard Tina; Jensen Eva Skafte; Rathje Marianne; White Jonathan; Wide Camilla (John Benjamins Publishing Company, 2025)
In this study, we investigate how differences and similarities in opening and closing greetings in professional emails in academia manifest themselves in Danish and Swedish. Our data consist of a corpus of 595 emails (primary data) and two surveys with 1836 respondents (supportive data). An important result is that cultural values, e.g., ideals of equality, in both language areas are expressed through similar linguistic means, but that due to different historical developments, the specific encoding is not identical. Another result is that there is a much larger variety in closing greetings than in opening greetings in both languages, which can be derived from the communication situation where openings and closings and the elements within these serve different purposes.
It's different with you: Contrastive perspectives on address research